Selection of Alternative Suppliers Using Analytical Hierarchy Process dan Technique For Order Preference By Similarity To Ideal Solution - Melani Magdalena Hutabarat; Agus Ristono; Sutrisno Sutrisno (OPSI, 2021)
Garment industry is an industry that focuses on manufacture of clothing. Along with the times, development model and function clothing is increasingly varied. Company’s effort is  determine best supplier. Based on observations in Central Java garment industry, it was found problems related to continuity of fabric supply from major suppliers. When demand soars, demand for cloth supply also increases. However, the availability of fabric supplies owned by main suppliers is not able to meet the needs of garment industry. Therefore, garment industry requires alternative backup suppliers who are able to meet the supply of fabric when the main supplier is inadequate. Supplier selection will be carried out using the Analytical Hierarchy Process (AHP) method in weighting and Technique for Others Preference by Similarity to Ideal Solution (TOPSIS) method in ranking priority order of suppliers. This supplier priority will be used as an alternative supplier that will meet the availability of fabric supply.